Does quality of sleep determine the menstrual cycle? A cross-sectional study on teenager - Susilowati, Dewi; Yulaikah, Siti; Nurlaili, Helmi (Malahayati International Journal of Nursing and Health Science, 2026)
Background: Irregularities in the menstrual cycle are a frequent occurrence and may negatively impact daily productivity. In Indonesia, approximately 32% of women aged 17–29 report experiencing irregular menstruation. Disturbances in sleep quality can interfere with melatonin and estrogen regulation, thereby contributing to menstrual cycle disruption. Purpose: To investigate the association between sleep quality and menstrual cycle regularity. Method: A cross-sectional design was employed involving 111 female students who met the inclusion criteria: maintaining records of the first day of menstruation between December 2024 and February 2025 and having no diagnosed reproductive system disorders. Sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI), while menstrual cycle data were obtained through questionnaires. Statistical analysis was performed using the chi-square test. Results: Among the respondents, 37 students (33.3%) with good sleep quality reported regular menstrual cycles, whereas 40 students (36%) with poor sleep quality experienced irregular cycles. The analysis yielded a p-value of 0.001, indicating statistical significance. Conclusion: Sleep quality was found to be significantly associated with menstrual cycle regularity.